Upadacitinib in active non-radiographic axial spondyloarthritis: 2-year data from the phase 3 SELECT-AXIS 2 study - Filip Van den Bosch; Atul Deodhar; Denis Poddubnyy; Walter P. Maksymowych; Désirée van der Heijde; Tae-Hwan Kim; Mitsumasa Kishimoto; Xenofon Baraliakos; Xianwei Bu; Ivan Lagunes-Galindo; In-Ho Song; Peter Wung; et al. (Arthritis Research & Therapy)
Abstract Background In SELECT-AXIS 2, upadacitinib improved the signs and symptoms of active non-radiographic axial spondyloarthritis (nr-axSpA) through 52 weeks versus placebo and was well tolerated. Here, we evaluated the efficacy and safety of upadacitinib through 2 years. Methods The study enrolled eligible adult patients with a clinical diagnosis of nr-axSpA who met the 2009 Assessment of SpondyloArthritis international Society (ASAS) classification criteria and had objective signs of active inflammation on magnetic resonance imaging (MRI) of sacroiliac joints and/or high-sensitivity C-reactive protein. Patients were randomized 1:1 to receive double-blinded treatment with upadacitinib 15 mg once daily (QD) or placebo for 52 weeks, after which all patients received open-label treatment with upadacitinib 15 mg QD. Efficacy results over 104 weeks were reported as observed (AO) and either AO with non-responder imputation (AO-NRI; binary endpoints) or AO with mixed-effect model for repeated measures (continuous endpoints). Treatment-emergent adverse events (TEAEs) were summarized through week 104. Results Of 313 patients randomized and treated, 224 (continuous upadacitinib n = 117; placebo/upadacitinib n = 107) completed 104 weeks of treatment. In patients who received continuous upadacitinib, sustained improvement was observed through 2 years of treatment across efficacy endpoints including disease activity, pain, function, enthesitis, quality of life, and MRI measures of inflammation. At week 104, 57.1%, 59.0%, and 31.4% of patients achieved ASAS40 response, and low disease activity and inactive disease (as defined by Axial Spondyloarthritis Disease Activity Score), respectively (AO-NRI); week 104 outcomes were generally similar in patients who initially received placebo and were switched to upadacitinib at week 52. In total, 286 patients were exposed to ≥ 1 dose of upadacitinib, comprising 378.3 patient-years (PY) of exposure. Upadacitinib was generally well tolerated, with exposure-adjusted event rates (EAERs) for TEAEs, serious adverse events (AEs), and AEs leading to study drug discontinuation of 207.5, 8.7, and 5.3 events/100 PY, respectively. EAERs of TEAEs of special interest were broadly consistent with those reported through week 52. Conclusions Treatment with upadacitinib demonstrated consistent improvement and maintenance of treatment effect across efficacy endpoints through 2 years; no new safety signals were identified with additional exposure. Trial registration NCT04169373.